A perfect match for district heating networks? An investigation of Power-to-Heat and Combined Heat and Power 2035 - Christian Furtwängler (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2025)
The recent energy crisis in Europe has underlined the importance of a fast replacement of fossil fuels like natural gas by green energy carriers. Great hopes for quick decarbonisation mostly rest on two technologies, hypothesized to form a "perfect match": Combined heat and power (CHP) generation units that are in widespread usage across district heating grids today are often planned to be decarbonized by using green fuels, e.g. green hydrogen originating from electrolysis with green electricity. Additionally, the direct usage of electricity for heating purposes (Power-to-Heat, PtH), is seen as a fitting complementing option. This contribution thus aims at investigating the cost structure of the CHP system of the future - and whether this perfect match is a likely outcome in different energy market environments. Three distinct mid-term scenarios for the year 2035 are developed and different heating portfolio setups are tested with regards to the viability of individual heating assets. For this analysis, the stochastic portfolio optimization framework StoOpt is used. The perfect match hypothesis is both theoretically confirmed and practically questioned by the obtained results. At least one of the technologies tends to struggle in different market environments and subsidies might be needed to secure investment in both technologies.
Keywords: 330; Combined Heat and Power; Power-to-Heat; Stochastic optimization; Long-term energy scenarios; District Heating